Penerapan Massage Effleurage dengan Virgin Coconut Oil (Vco) Terhadap Resiko Dekubitus pada Pasien Tirah Baring di Wilayah Kerja Puskesmas Kartasura - Rikha Mutiara Kusuma Mukti; Ika Silvitasari (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Bed rest is one of the factors that can cause skin integrity disorders. Bed rest for a long time can cause physiological changes in the patient's body system, one of which can cause the appearance of decubitus in the integument system. The treatment technique that can be given is by giving Effleurage Massage with Virgin Coconut Oil. To find out the results of the implementation of Effleurage Massage with Virgin Coconut Oil on the Risk of Decubitus in Bed Rest Patients in the Kartasura Health Center Working Area. This research used a descriptive design on 2 (two) male respondents aged 63 and 78 years which was conducted from 4 June - 6 June 2024 in Singopuran Village, Kartasura, Sukoharjo with each respondent being given massage intervention for 3 consecutive days. join in. The instrument used is the Braden Scale to measure the level of skin integrity score. There was an increase in the Braden scale score between before and after application to Mr. S and Mr. N. The application of Effleurage Massage with Virgin Coconut Oil is effective in increasing the skin integrity score in bed rest sufferers who are at risk of pressure ulcers in Singopuran Village, Kartasura, Sukoharjo.